Factors Influencing User's Intention to Play in Innovative Mobile Gaming Usage - Laksmana, Jason Aditya; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2016)
Abstract.The games industry changed in the last decade from a market dominated by consoles and online gaming publishers, to the new and increasing shifts in the mobile gaming sector. Based on the research report by various research firms such as Newzoo and Digi-Capital, the mobile gaming industry made 29 billion in 2015 and it’s going to continue growing (with the estimation could produce as high as 49 billion by 2018). This study was examining the factors influencing customers’ mobile game preferences, and factors affecting users’ intention to play. This study also examining the customers’ enthusiasm toward Valve (a game developer company) if they decides to launch their games into mobile game platforms, due to the increasing trends in mobile gaming industry. The findings of the study can be used to provide the mobile game developer companies better understanding about the consumers’ behavior regarding the mobile gaming. The variables that was used in this study was constructed by combining the variables from previous research about intention to play mobile games. Perceived enjoyment, behavior, subject norm, time flexibility, network externalities, and flow experience are the predicted variables that influences customer intention to play. Judgmental and snowball sampling was performed to 420 respondents in Bandung, Jakarta, Solo, Semarang, Yogyakarta, Surabaya, Medan, and Jambi, which mostly consists of high school and university students. Online questionnaire was developed to gather the data. Data processed through confirmatory factor analysis, linear regression, and ANOVA. This research finds that the factors that influences customers’ preferences are the price of the game, game genres, and the reputation of the developers. While the genre of the games that people like to play the most is casual games. Time flow has the strongest influence to intention to play, and followed by subject norm, perceived enjoyment, and behavior. Meanwhile, network externalities and flow experience have no influence towards intention to play. The mobile game developer companies should pay attention about these factors, since it could enhance customers’ level of intention to play, and by understanding the customer preferences, it could generate more profits and revenue. Furthermore, based on the research conducted before, Valve has good brand awareness and the consumer enthusiasm level is high. So if Valve decides to launch their games in mobile platform, while at the same time also pay attention to the factors affecting customers’ preferences and factors influencing customers’ intention to play, they should be successful.Keywords: mobile gaming, customer enthusiasm, influencing factor, intention to use